DURABILITAS KOLOM BETON TULANGAN BAMBU TERHADAP PENGARUH SUHU TINGGI - Wardana, Erik Fadilah Kusuma; Umniati, B. Sri; Risdanareni, Puput (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2025)
Reinforced concrete plays a crucial role in structural systems by providing strength and stability to buildings. Recent advancements in construction technology have introduced bamboo as an alternative reinforcement material to steel, due to its relatively high tensile strength (up to 253 MPa). However, bamboo's high cellulose content increases its vulnerability to fire. During building fires, structural elements may be exposed to temperatures between 800–1000°C for up to one hour. This study aims to investigate the effect of elevated temperatures on the axial load capacity and strain behavior of bamboo-reinforced concrete columns. Two reinforcement types were tested: (1) intact round bamboo with spiral steel stirrups, and (2) slatted bamboo with rectangular steel stirrups. All specimens were made using 25 MPa concrete with dimensions of 15×15×60 cm, and were exposed to 800°C for one hour before testing. Results showed that the round bamboo column with spiral stirrups sustained a maximum axial load of 247.6 kN (4.67% lower than analytical predictions and 59.83% lower than pre-fire values). The slatted bamboo column with rectangular stirrups held 233.2 kN (4.18% lower analytically and 61.78% lower than pre-fire values). Axial and lateral strain values varied slightly between specimens. This research highlights the structural viability of bamboo reinforcement under high-temperature exposure. Keywords: High Temperature Effect; Concrete Column; Bamboo Reinforced Concrete.